Mobile Wallet Promotions and Consumer Purchase Frequency in E-Commerce - Heriyanto (SAFE-Network, 2025)
This study aims to examine the influence of mobile wallet promotions on consumer purchase frequency in e-commerce, considering the mediating roles of perceived usefulness and perceived ease of use. A quantitative explanatory approach was employed using a survey method involving 116 active mobile wallet users of GoPay, OVO, and DANA in Indonesia. Data were collected through an online questionnaire using a five-point Likert scale and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4 software. The results reveal that mobile wallet promotions have a positive and significant effect on perceived usefulness, perceived ease of use, and consumer purchase frequency, both directly and indirectly. The R² value of 0.642 indicates that promotional, usefulness, and ease variables explain 64.2% of the variance in consumer purchasing behavior. These findings support the Technology Acceptance Model (TAM) and Stimulus–Organism–Response (S–O–R) framework as robust theoretical bases for understanding digital purchasing behavior. Practically, the study offers insights for e-commerce platforms and digital wallet providers to design sustainable and personalized promotion strategies that enhance user satisfaction and long-term loyalty.